2019
DOI: 10.1002/pmic.201800387
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Liver Proteome and Identification of Critical Proteins Affecting Milk Fat, Protein, and Lactose Metabolism in Dariy Cattle with iTRAQ

Abstract: In this study, the proteomes of liver tissues are investigated in three periods of the lactation cycle of Holstein cows by using isobaric tag for relative and absolute quantification (iTRAQ) technique to obtain liver proteome and identify functional proteins/genes involved in milk synthesis in dairy cattle. Based on iTRAQ analysis, 3252 proteins are detected in the liver tissues (false discovery rate ࣘ0.01). Thirty-two differently expressed proteins (DEPs) are identified during the three periods by p-value <0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 78 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…These findings were consistent with previous liver proteome [21], and transcriptome [22] studies that have reported enrichment of carbohydrates, lipids, and protein metabolism-related pathways in the early and/or peak of lactation compared to the dry period to support milk synthesis. Since none of the cows in any treatment group showed any signs of metabolic disorders, all these massively enriched pathways could be considered as conventional metabolic adaptations to preserve whole-body metabolic homeostasis during the NEB period.…”
Section: Gene Ontology and Functional Enrichment Analyses Of Differen...supporting
confidence: 92%
See 1 more Smart Citation
“…These findings were consistent with previous liver proteome [21], and transcriptome [22] studies that have reported enrichment of carbohydrates, lipids, and protein metabolism-related pathways in the early and/or peak of lactation compared to the dry period to support milk synthesis. Since none of the cows in any treatment group showed any signs of metabolic disorders, all these massively enriched pathways could be considered as conventional metabolic adaptations to preserve whole-body metabolic homeostasis during the NEB period.…”
Section: Gene Ontology and Functional Enrichment Analyses Of Differen...supporting
confidence: 92%
“…The over-abundance of ACO2, DLST, IDH1, IDH2, MDH2, and PCK1 related to the TCA cycle, as well as the over-abundance of ACAT1, and HMGCS1 involved in ketogenesis, in the PP period relative to the AP period, strengthened the robustness of the proteome analysis and the ASCA analysis. Indeed most of them were previously identified by differential proteome during the transition period [11,21,[23][24][25]. Some proteins may be highlighted such as the overabundance of both the ACO2 and IDH mitochondrial enzymes known to induce αketoglutarate (AKG) production (from citrate) that serves as an energy source and also as a precursor for glutamine, gluconeogenesis, and synthesis of acute-phase proteins [26].…”
Section: Gene Ontology and Functional Enrichment Analyses Of Differen...mentioning
confidence: 99%
“… He et al (2018) performed an iTRAQ-based quantitative proteomic analysis of horn tissues from both scurs and normal two-horned and four-horned individuals; their results indicated that the PI3K-Akt signaling pathway was the most significant, possibly affecting the formation of the extracellular matrix in horn that ultimately leads to the development of deformed horn tissue. Xu et al (2019) used iTRAQ to identify critical proteins affecting milk fat in dairy cattle. Using the iTRAQ approach, Li et al (2017) examined 27 fiber samples representing nine fiber types from sheep and goats and found differentially abundant proteins that are important to the structural components of hair, as well as some genes related to hair growth and fatty acid synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…APOA4, a lipid-binding protein, is involved in the synthesis of cholesterol, steroids, and other lipids, and improves glucose homeostasis ( 72 ). The anti-inflammatory and antioxidant activities of APOA4 are crucial for maintaining hepatic homeostasis ( 73 , 74 ). In our study, APOA4 was downregulated, indicating that Cd injury affected fat metabolism, inflammation, and oxidative stress in the liver.…”
Section: Discussionmentioning
confidence: 99%